Navigating Globalization and Disruption: A Review of Sustainable Management Strategies for Islamic Educational Institutions in Pakistan - Syed Farroukh Shah (PT. Berkah Smart Academica, 2025)
This research explores sustainable management strategies in Islamic Educational Institutions (IEIs) in Pakistan in the face of the dual challenges of globalization and technological disruption. The primary issue addressed is the tension between traditional madrasah management models and global digital competency demands that trigger graduate marginalization. This study aims to formulate an adaptive managerial framework while maintaining the integrity of Islamic values. Using the Systematic Literature Review (SLR) method with the PRISMA protocol on 50 reputable journals from 2021-2025, data were analyzed using qualitative content analysis techniques. Research results show that IEIs in Pakistan have adopted hybrid management models through STEM curriculum synchronization, AI-based administrative digitalization, and optimization of productive waqf for financial independence. In conclusion, an effective sustainable management strategy for IEIs is the integration of dynamic technological capabilities with Maqasid al-Shariah-based leadership, which is proven to increase institutional resilience in the midst of the disruption era.